'We will take them from anywhere': Schools working within multiple initial teacher training partnerships - Mutton, T; Butcher, J (2008)
This article reports on a small-scale study focusing on the role of the initial teacher training (ITT) coordinator in schools in England in terms of working simultaneously across and within a number of different ITT partnerships. Data collection involved a review of the relevant course documentation of the four main higher education institutions working in one region, a postal questionnaire to 113 primary schools and secondary schools within that region and semi-structured telephone interviews with six school-based ITT coordinators. The data were analysed within broad categories identifying the facilitators and constraints of carrying out the role when working in partnership with a number of different ITT providers. The findings indicate that there is a developing trend towards schools in England working with multiple partners, particularly in the case of secondary schools and that, notwithstanding the administrative difficulties sometimes caused, there are clear perceived advantages to working in such a way, both for the schools themselves and for the trainees in those schools. The implications of this in terms of partnerships between schools and ITT providers are explored, as are the potential opportunities for the development of the school coordinator's role.